Identification of Helicoverpa armigera promoters for biotechnological applications. (March 2022) - Samantsidis, George-Rafael; Denecke, Shane; Swevers, Luc; Skavdis, George; Geibel, Sven; Vontas, John
Abstract: Helicoverpa armigera and Helicoverpa zea are highly polyphagous major agricultural pests with a global distribution. Their control is based on insecticides, however, new, effective, and environmentally friendly control tools are required to be developed and validated. In an effort to facilitate the development of advanced biotechnological tools in these species that will take advantage of new powerful molecular biology techniques like CRISPR/Cas9, we used available transcriptomic data and literature resources, in order to identify RNA polymerase II and III promoters active in RP-HzGUT-AW1(MG), a midgut derived cell line from Helicoverpa zea . Following functional analysis in insect cell lines, four RNA polymerase II promoters from the genes HaLabial, HaTsp-2A, HaPtx-I and HaCaudal were found to exhibit high transcriptional activity in vitro . The HaTsp-2A promoter did not exhibit any activity in the non-midgut derived cell lines Sf-9 and Hi-5 despite high sequence conservation among Lepidoptera, suggesting that it may function in a gut specific manner. Furthermore, considering the utility of RNA polymerase III U6 promoters in methodologies such as RNAi and CRISPR/Cas9, we identified and evaluated four different U6 promoters of H. armigera . In vitro experiments based on luciferase and GFP reporter assays, as well as in vivo experiments targeting an essential gene of Helicoverpa, indicate that these U6 promoters are functional and can be used to experimentally silence or knockout target genes through the expression of shRNAs and sgRNAs respectively. Taking our findings together, we provide a set of promoters useful for the genetic manipulation of Helicoverpa species, that can be used in various applications in the context of agricultural biotechnology. Graphical abstract: Image 1 Highlights: Four strong H. armigera midgut promoters are identified and characterized functionally. H. armigera U6 promoters drive efficient RNAi in lepidoptera cell lines (RP-HzGUT-AW1(MG) and Sf-9). H. armigera U6 promoters are incorporated in CRISPR vectors. U6 promoters drive expression of sgRNAs against GFP (proof-of-concept).